A Climate of Misogyny: Gender, Politics of Ignorance, and Climate Change Denial – An Interview with Katharine Hayhoe. Issue 110 (2nd October 2021) - Bjork-James, Sophie; Barla, Josef
ABSTRACT: In this interview, climate scientist Katharine Hayhoe discusses with Sophie Bjork-James and Josef Barla: the issue of gender inequality in the natural sciences; the toxic entanglement of right-wing extremism, sexism and anti-science rhetoric in discourses on climate change; the far-reaching institutional and social consequences of the Trump administration's attacks on climate science research and advocacy; as well as the politics of ignorance and promising ways to rebuild trust in shared values and a shared world in the face of multiple planetary crises and challenges from climate change to biodiversity loss to the rise of far-right extremism.